Adjustments during crisis: government expenditures and revenues in Latin America, 1975 - 1988 - Hicks, Norman (Estudios de Economía, 2016)
This study examines public expenditure and revenue data for 15 Latin American countries for the period 1975-1988, although, the focus of the analysis is generally on the period of 1979-1988 during which fundamental changes in public finance and external economic relations were occurring. The study focuses largely on consolidated central government expenditures, which exclude public enterprises, and generally relies on unweighted averages of the individual country data. Overall, the study notes that after 1980, budget deficits rose from about 2 percent of GDP to a peak of about 6 percent in 1982. After 1982 there was a slight decline in the overall deficit, but they nevertheless averaged about 5 percent of GDP in 1988. The increase in the average deficit can be attributed largely to an increase in current expenditures, which rose from 15 percent to about 20 percent of GDP. However, only about half of the increase in current expenditures was due to an increase in interest expenses